Tensile and fatigue properties of the binder jet printed and hot isostatically pressed 316L austenitic stainless steel - Kumar, Punit (2023)
The binder jet printed (BJP) metallic components are not yet considered for widespread structural applications that involve cyclic loading conditions due to the high levels of porosity typical to them. In the present study, the porosity in BJP 316L stainless steel (SS) was reduced from 3.5-5.6% to 1–1.2% by improving process parameters first and then employing the post-processing hot iso-static pressing (HIP) treatment. The reduced porosity in the as-sintered conditions resulted in ⁓15 and 5% improvement in tensile yield and ultimate tensile strengths, respectively. However, the high cycle fatigue strength (⁓250 MPa) did not improve even after a ⁓fivefold reduction in the porosity. HIP resulted in a further reduction in the porosity, which improved the elongation to failure by 30% while reduced the yield strength by ∼10% (due to grain coarsening that occurred during HIP). It, however, did not improve the unnotched fatigue strength. The microstructural coarsening during HIP also affected the short fatigue crack growth resistance of the BJP 316L SS specimens. Moreover, after reduction in overall porosity and the size of the pores, the void and fatigue crack nucleation mechanisms during tensile and fatigue loadings changed from pore assisted to inclusion assisted.